Maternal plasma extracellular vesicles tsRNA as potential biomarkers for assessing preterm labor risk - Xinrui Sun; Ying Feng; Liang Xie; Yilun Wu; Jia Mao; Yi Zhang; Linyu Zhang; Xin Yuan; Jiangping Ni; Xue Xiao; Hanmin Liu; Li Dai; et al. (BMC Pregnancy and Childbirth)
Abstract Background Spontaneous preterm labor (PTL) accounts for approximately 70% of preterm births, posing significant risks to both maternal and neonatal health. Current predictive biomarkers lack sufficient reliability, underscoring the need for non-invasive and dependable indicators. Emerging research indicates that tRNA-derived small RNAs (tsRNAs) are involved in various diseases; however, their potential association with PTL remains underexplored. Methods Bioinformatics analyses of public GEO datasets (PRJNA415953 and PRJNA428989) were conducted to identify tsRNAs associated with PTL. Validation was performed using plasma extracellular vesicles samples collected at 12 weeks of gestation from PTL patients (n = 45) and healthy controls (n = 38). Functional assays were used to assess the impact of tsRNA1 (tRNA-Gly-GCC-5p-tRF-921) on extravillous trophoblast (EVT) function, including apoptosis, migration, invasion, and endothelial-like tube formation in HTR8/SVneo cells. Transcriptomic sequencing was conducted to identify tsRNA1-mediated pathways, and DNA methylation patterns were predicted based on the transcriptomic data. Statistical significance was determined using Student’s t-test. Results Two tsRNAs, tsRNA1 and tsRNA3 (tRNA-Gly-GCC-5p-tR-half-368), were significantly upregulated in PTL patient samples compared to controls. Overexpression of tsRNA1 impaired EVT function, increased apoptosis, and altered DNA methylation profiles, implicating its critical role in PTL mechanisms. Conclusions This study identifies tsRNA1 as a key regulator of EVT dysfunction and placental pathology in PTL. The findings provide novel insights into the mechanistic role of tsRNAs in PTL and highlight tsRNA1 as a promising biomarker for early risk stratification and prediction of the condition. Clinical trial number Not applicable.